Down-regulation of the brain-specific cell-adhesion molecule contactin-3 in tuberous sclerosis complex during the early postnatal period - Korotkov, Anatoly; Luinenburg, Mark J; Romagnolo, Alessia; Zimmer, Till S; van Scheppingen, Jackelien; Bongaarts, Anika; Broekaart, Diede W M; Anink, Jasper J; Mijnsbergen, Caroline; Jansen, Floor E; van Hecke, Wim; Spliet, Wim G; et al. (Journal of neurodevelopmental disorders, 2022)
BACKGROUND: The genetic disorder tuberous sclerosis complex (TSC) is frequently accompanied by the development of neuropsychiatric disorders, including autism spectrum disorder and intellectual disability, with varying degrees of impairment. These co-morbidities in TSC have been linked to the structural brain abnormalities, such as cortical tubers, and recurrent epileptic seizures (in 70-80% cases). Previous transcriptomic analysis of cortical tubers revealed dysregulation of genes involved in cell adhesion in the brain, which may be associated with the neurodevelopmental deficits in TSC. In this study we aimed to investigate the expression of one of these genes - cell-adhesion molecule contactin-3. METHODS: Reverse transcription quantitative polymerase chain reaction for the contactin-3 gene (CNTN3) was performed in resected cortical tubers from TSC patients with drug-resistant epilepsy (n = 35, age range: 1-48 years) and compared to autopsy-derived cortical control tissue (n = 27, age range: 0-44 years), as well as by western blot analysis of contactin-3 (n = 7 vs n = 7, age range: 0-3 years for both TSC and controls) and immunohistochemistry (n = 5 TSC vs n = 4 controls). The expression of contactin-3 was further analyzed in fetal and postnatal control tissue by western blotting and in-situ hybridization, as well as in the SH-SY5Y neuroblastoma cell line differentiation model in vitro. RESULTS: CNTN3 gene expression was lower in cortical tubers from patients across a wide range of ages (fold change = - 0.5, p < 0.001) as compared to controls. Contactin-3 protein expression was lower in the age range of 0-3 years old (fold change = - 3.8, p < 0.001) as compared to the age-matched controls. In control brain tissue, contactin-3 gene and protein expression could be detected during fetal development, peaked around birth and during infancy and declined in the adult brain. CNTN3 expression was induced in the differentiated SH-SY5Y neuroblastoma cells in vitro (fold change = 6.2, p < 0.01). CONCLUSIONS: Our data show a lower expression of contactin-3 in cortical tubers of TSC patients during early postnatal period as compared to controls, which may affect normal brain development and might contribute to neuropsychiatric co-morbidities observed in patients with TSC.
Keywords: dospělí; Infant; dítě; předškolní dítě; novorozenec; Adult; mladý dospělý; kontaktiny; Adolescent; lidé; Infant, Newborn; mozek; poruchy autistického spektra; Down-Regulation; Tuberous Sclerosis; kojenec; Brain; Child, Preschool; Young Adult; tuberózní skleróza; lidé středního věku; Child; down regulace; Autism Spectrum Disorder; Contactins; Middle Aged; mladiství; Humans